Fallow Replacement Crop (Cover Crops, Annual Forages, and Short-Season Grain Crops) Effects on Available Soil Water - J. D. Holman; T. Roberts; S. Maxwell; I. Kisekka; A. Obour (Kansas Agricultural Experiment Station Research Reports, 2015)
Producers are interested in growing cover crops and reducing fallow. Limited information is available on growing crops in place of fallow in the semiarid Great Plains. Between 2012 and 2015, spring cover, annual forage, and grain crops were grown in place of fallow in a no-till wheat-grain sorghum-fallow (WSF) rotation in southwest Kansas. Growing a cover, hay, or grain crop in place of fallow reduced the amount of stored soil moisture at wheat planting. On average, cover crops stored slightly more moisture than hay crops, but this soil moisture difference did not affect wheat yields. Soil moisture after grain crops was less than after cover or hay crops, and this difference resulted in reduced wheat yields. These results do not support claims that cover crops increase soil moisture compared to fallow. Soil moisture storage from fallow crop termination to wheat planting was greatest among those treatments that were most dry at termination and produced the most aboveground biomass. On average, cover crops had a 28% precipitation storage efficiency (PSE) and hay crops had a 22% PSE between termination and wheat planting. Fallow during the full-fallow period (sorghum harvest to wheat planting) had an 18% PSE. Crops grown in place of fallow must compensate for the expense of growing the crop plus the reduction in soil moisture for the next crop.
Keywords: fallow; cover crops; annual forages; short-season grain; soil water; water use efficiency; precipitation storage efficiency